New England nightmares : true tales of the strange and gothic - McQueen, Keven (Indiana University Press, 2018)
New England is infamous as the setting for unexplained deaths, ghost stories, and bizarre murders. An intriguing and frightful look into the odder side of the Northeast, New England Nightmares promises to send chills down your spine.